Persepsi Warga Tentang Lokasi dan Harga di Indomaret yang Dapat Mempengaruhi Pengembalian Keputusan Pembelian Konsumen : Studi Kasus Indomaret Cabang Desa Purwobinagun - Ema Kirani; Putri Mauliza; Tri Auri Yanti (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This research aims to examine residents' perceptions of the influence of location and price on purchasing decisions at Indomaret, Purwobinangun Village, Langkat Regency. The background to this research is based on the phenomenon of the increasing number of modern retail outlets penetrating rural areas, which were previously dominated by traditional markets. The presence of Indomaret as the only modern retail in this area creates challenges for local stalls and creates differences in prices and ease of access for consumers. The research used a qualitative descriptive approach with an interview method with residents of Purwobinangun Village and its surroundings as informants. The research results show that even though Indomaret's location is far from the city center, local people feel that the location is strategic because it is close to their settlements and easy to access. Apart from that, the price difference with local shops is considered reasonable, and promotions held by Indomaret increasingly attract consumers to shop. In conclusion, location and price factors at Indomaret play a significant role in influencing village community purchasing decisions. This research is important to understand the adaptation of village communities to modern retail and apply it to local market development.